Graduan dan alam pekerjaan: kes siswazah UKM - Ishak Yussoff ,; Rahmah Ismail ,; Robiah Sidin, (Universiti Kebangsaan Malaysia, 2008)
Nowadays job market is getting more dynamic due to rapid changes in technology and diversity of employers’ requirements. Consequently, this raises various issues in the job market, and it has been worsened by unfavourable current national economic performance. Slow new jobs creation is not in tandem with the number of graduates flooding the job market. This situation has created stiff competition among the graduates and subsequently raises unemployment problem, to the extent that some graduates are forced to accept whatever the employer, leaving no options, has offered. This phenomenon has significant implication on employability and job satisfaction among the graduates. The purpose of this article is to discuss these issues with special reference on UKM’s graduates. Our analyses are based on a survey conducted using questionnaires to 343 UKM’s graduates whom completed their studies between 1998 and 2002. Aspects that are examined in this article include duration taken for first employment, suitability of field of studies with occupation and the level of job satisfaction among the graduates.